Database and geospatial mapping study of those eligible for extracorporeal cardiopulmonary resuscitation in the Thames Valley Region, England - Oscar Millerchip; Jasper Eddison; Alex Rosenberg; Jon Bailey; James Raitt (Resuscitation Plus)
Background: Out-of-hospital cardiac arrest survival remains low. Extracorporeal-cardiopulmonary resuscitation (ECPR) is a therapy for refractory out-of-hospital cardiac arrest that can improve survivability by decreasing the time a patient is without adequate perfusion, the low-flow time. Access to ECPR is limited by the number, location and delivery approach of centres offering this therapy. Aims: This study aims to identify how many patients are eligible for ECPR in the Thames Valley area and provide geographical analysis to appraise the specialist-centre approach of ECPR delivery in the region. Methods: Data from out-of-hospital cardiac arrests attended by the Thames Valley Air Ambulance from 1st Jan 2022 to 1st Jan 2024 were reviewed for eligibility to receive ECPR against inclusion criteria. Eligible cases were modelled using Geographic Information System software, and spatial autocorrelation analysis was performed to identify any significant ‘hotspots’, ‘cold spots’, or significant geographical distribution of eligible cases. Results: Of some 1,182 cardiac arrests attended, 188 (16%) cases were eligible under inclusion criteria for ECPR. In 2023 seven patients received ECPR, all focussed in a small area of the Thames Valley. The majority of eligible cases fall outside of the catchment of any one hospital when utilising the hospital-based or rendez-vous models of ECPR. Global Moran’s analysis of the entire region found no significant clustering or dispersal, suggesting a near-random distribution despite some evidence of hotspots. Conclusion: ECPR can improve survival for out-of-hospital cardiac arrest, but time constraints preclude access to this therapy for many, which affects equitability across a geographical area. Geospatial analysis techniques can aid in reviewing the optimal delivery methods of ECPR and improve equitable geographical access to services. The methodology described may aid other organisations in planning the delivery of ECPR.